Targeted Reactivation of FMR1 Transcription in Fragile X Syndrome Embryonic Stem Cells - Haenfler, Jill M.; Skariah, Geena; Rodriguez, Caitlin M.; Monteiro da Rocha, Andre; Parent, Jack M.; Smith, Gary D.; Todd, Peter K. (Frontiers in Molecular Neuroscience, 2018)
Fragile X Syndrome (FXS) is the most common inherited cause of intellectual disability and autism. It results from expansion of a CGG nucleotide repeat in the 5’ untranslated region of FMR1. Large expansions elicit repeat and promoter hyper-methylation, heterochromatin formation, FMR1 transcriptional silencing, and loss of the Fragile X protein, FMRP. Efforts aimed at correcting the sequelae resultant from FMRP loss have thus far proven insufficient, perhaps because of FMRP’s pleiotropic functions. As the repeats do not disrupt the FMRP coding sequence, reactivation of endogenous FMR1 gene expression could correct the proximal event in FXS pathogenesis. Here we utilize the CRISPR/dCAS9 system to selectively re-activate transcription from the silenced FMR1 locus. Fusion of the transcriptional activator VP192 to dCAS9 robustly enhances FMR1 transcription and increases FMRP levels when targeted directly to the CGG repeat in human cells. Using a previously uncharacterized FXS human embryonic stem cell (hESC) line which acquires transcriptional silencing with serial passaging, we achieved locus-specific transcriptional re-activation of FMR1 mRNA expression despite promoter and repeat methylation. However, these changes at the transcript level were not coupled with a significant elevation in FMR protein expression in FXS cells. These studies demonstrate that directing a transcriptional activator to CGG repeats is sufficient can selectively reactivate FMR1 mRNA expression in Fragile X patient stem cells.